Disharmony in the Appointment of Beneficiaries in Life Insurance Policies with the Legal Provisions of Inheritance in Indonesia - Desta Dwi Alfian; Rois Harliyanto (Riviera Publishing, 2026)
The appointment of beneficiaries in life insurance policies often creates legal conflicts with inheritance law provisions in Indonesia, particularly when the designated beneficiary is not a legal heir. This disharmony arises from the tension between the principle of freedom of contract in insurance law, which grants policyholders the authority to designate beneficiaries, and the protection of heirs’ mandatory inheritance rights (legitime portie) under inheritance law. This research aimed to examine the inconsistencies between Indonesian inheritance law and the designation of beneficiaries in life insurance policies. Conflicts may occur when the beneficiaries specified in insurance policies do not correspond with the legally recognized heirs. This study employed a normative juridical method using statutory, conceptual, and case approaches, supported by interviews with insurance practitioners and legal academics. The findings revealed a conflict between inheritance law provisions and the contractual freedom applied in the insurance sector, particularly regarding the protection of heirs’ mandatory rights (legitime portie). Legal uncertainty also results from the absence of clear and harmonized regulations within the Indonesian legal system concerning the position and rights of heirs in relation to life insurance benefits. Based on these findings, regulatory harmonization is required to establish legal certainty and provide protection for all relevant parties, including insurance companies, policyholders, and heirs. Such harmonization is essential to maximize the function of life insurance as a financial planning and protection instrument while minimizing potential inheritance disputes.